COGNITION AND NORMS: A CONCEPTUAL FRAMEWORK TO ADDRESS DENIALISM AND DISSONANT COMMUNICATION IN SOCIAL DILEMMAS - Meyer, Leandro Frederico Ferraz (Seven Editora, 2025)
How to explain denialism, resistance to health measures, and the proliferation of narratives contrary to what was supposed to be common sense? Although a possible answer to this question points to demographic, social and economic differences, the article aims to expose the decisive influence of individuals' mental models and value systems. In preparation for testing these connections, we have introduced a conceptual framework that integrates the Habermasian approach to communication with the psychology of moral development and the Bloomington School of institutional analysis. Results from experiments reported elsewhere support the hypothesis that the ability to resolve social dilemmas communicatively, without coercion, requires social perspectives and cognitive structures that emerge late from the order of individuals' moral development.DOI: https://doi.org/10.56238/sevened2024.037-196